Ultrasonic-assisted enzymatic extraction and antioxidant activity of polysaccharides from Setaria viridis. Issue 11 (23rd July 2016) - Li, Le; Li, Xu; Ding, Chunbang; Yuan, Shu; Zhang, Zhongwei; Chen, Yanger; Hu, Chao; Yuan, Ming
ABSTRACT: Ultrasonic-assisted enzymatic extraction (UEAE) and response surface methodology (RSM) were used to isolate polysaccharides from Setaria viridis (SVP). Optimal extraction conditions in the enzymatic hydrolysis process were: extraction duration, 68 min; extraction temperature, 51°C; ratio of enzyme to raw material, 1.6%; and ratio of liquid to raw material, 20 mL/g. Then, following ultrasonic treatment (180 W, 60°C, 60 min), the experimental yield was 8.94 ± 0.38%. Crude SVP was purified by DEAE cellulose-52 chromatography and Sephadex G-100 chromatography, resulting in the isolation of three fractions (designated SVP-1, SVP-2 and SVP-3). These SVPs were mainly composed of glucose residue, and SVP-3 had a significantly higher uronic acid content than the other two fractions. Additionally, all fractions showed strong antioxidant activities in vitro .